THE INFLUENCE OF LOCATION, TIME AND SUPERVISION WITH COMPLAINT HANDLING AS INTERVENTION VARIABLES ON THE EFFECTIVENESS OF PARKING MANAGEMENT IN KARIMUN REGENCY - Syamsudin; Ramli; Mohammad Gita Indrawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The contribution of the Karimun Regency Transportation Agency in efforts to increase local revenue in the parking service program for 2023 to 2024 was not realized as targeted, due to problems in handling complaints receiving the lowest score in the SKM and there were significant differences in the achievement of targets in each location zone and at each parking time. Furthermore, the parking management supervision system by the Transportation Department has not been optimally implemented across all areas. This mixed-method research is limited and focused on examining the influence of location zones, time, and supervision with complaint handling as an intervening variable on the effectiveness of parking management. It is concluded that supervision and complaint handling have a significant effect on the effectiveness of parking management, while location zones and time are not significant. Furthermore, location zones and supervision have a significant effect on complaint handling, but time does not. Furthermore, complaint handling is able to significantly intervene in the effect of location zones and supervision on the effectiveness of parking management, but it is not able to significantly intervene in the effect of time on the effectiveness of parking management. It is recommended that the Karimun Regency Transportation Agency optimize officer responses to parking-related issues and balance the duration of vehicle parking with the fees that must be paid by the public. It is recommended that the Karimun Regency Transportation Agency optimize the response of officers to parking-related issues and balance the duration of vehicle parking with the fees that must be paid by the community for parking, by prioritizing suggestions and input from the surrounding community regarding parking that is organized and at times when problems and violations related to parking are likely to occur. as well as to optimize the achievement of targets for each parking time slot that has not been optimally achieved, by identifying problems encountered through the parking-related complaint channel and gathering input from parking service users, to be followed up with solutions and alternatives to optimize the effectiveness of parking management.